Tophaceous Gout in the Pancreas: Case Reports and Review of the Literature - Choi, Soo; Voskanian, Natalie; Ramos, Jeffrey; Nguyen, Katherine H.Y. (Case Reports in Rheumatology, 2022)
We report 3 patients who presented with abnormal pancreatic contents that were initially nondiagnostic but were eventually found to have urate crystal deposition consistent with pancreatic tophaceous gout. Our first case involved an ICU patient who had fever of unknown origin and refractory pancreatic pseudocyst. The other 2 patients presented with abdominal pain associated with a pancreatic mass which mimicked malignancy. After further investigation, we were able to identify pancreatic tophaceous gout as the diagnosis. Initiation of therapy led to resolution of pancreatitis in the first patient and resolution of abdominal pain and decrease in size of a pancreatic mass in the other 2 patients. The recognition of clinical gout involving the pancreas has important implications in the evaluation and care of these patients who are at high risk for tophaceous gout. In addition, the importance of specimen preparation that preserves crystals for viewing is discussed.